The Strategies of Teaching English Using Differentiated Learning in Junior High School in Sekolah Penggerak in North Tapanuli academic year 2024/2025 - Rumahorbo, Rostetty S; Sinambela, Erika; Manurung, Lastri W (Pascasarjana Universitas HKBP Nommensen, 2024)
Differentiated Learning is the process of tailoring lessons to meet each student's interests, needs, and strengths, the goal of this research is to analyze the teachers’ strategies and obstacles in using differentiated learning in Sekolah penggerak. The subjects were four teachers from the Sekolah Penggerak namely SMP Negeri 4 Pahae Julu and SMP Negeri 2 Siatas Barita in North Tapanuli in North Sumatra. Interviews, observation, and documentation were applied to collect the data. Qualitative descriptive was the type of approach used in this study. The data was analyzed using triangulation consisting of three stages, namely data reduction, data presentation, and conclusion Strategies used by the teachers to accommodate the students' needs were the differentiated content, process, and product by mapping the students’ needs based on the students’ readiness, interests and learning profiles. Thus, this research concludes that the strategies in differentiated learning in class were effective and could help the students to understand the material according to the student’s needs. For further research, the researcher might scrutinize the effectiveness of differentiated learning in teaching English for student outcomes and the schools, the obstacles in teaching using differentiated learning were, that the teachers should facilitate workshops or training about differentiated learning.